Solve for m 7/8*(m-13)=14

Math
78⋅(m-13)=14
Multiply both sides of the equation by 87.
87⋅78⋅(m-13)=87⋅14
Simplify both sides of the equation.
Tap for more steps…
Simplify 87⋅78⋅(m-13).
Tap for more steps…
Cancel the common factor of 8.
Tap for more steps…
Cancel the common factor.
87⋅78⋅(m-13)=87⋅14
Rewrite the expression.
17⋅7⋅(m-13)=87⋅14
17⋅7⋅(m-13)=87⋅14
Cancel the common factor of 7.
Tap for more steps…
Cancel the common factor.
17⋅7⋅(m-13)=87⋅14
Rewrite the expression.
1⋅(m-13)=87⋅14
1⋅(m-13)=87⋅14
Multiply m-13 by 1.
m-13=87⋅14
m-13=87⋅14
Simplify 87⋅14.
Tap for more steps…
Cancel the common factor of 7.
Tap for more steps…
Factor 7 out of 14.
m-13=87⋅(7(2))
Cancel the common factor.
m-13=87⋅(7⋅2)
Rewrite the expression.
m-13=8⋅2
m-13=8⋅2
Multiply 8 by 2.
m-13=16
m-13=16
m-13=16
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Add 13 to both sides of the equation.
m=16+13
Add 16 and 13.
m=29
m=29
Solve for m 7/8*(m-13)=14

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top